Application of Plackett–Burman and Box–Behnken designs to develop a sensitive and robust HPLC method for quantifying hypolipidemic drugs, rosuvastatin and bempedoic acid in tablets - Susmitha Aggarapu; Rajitha Galla; Neha Jabeen Shaik; Sai Jyothi Dasari (Future Journal of Pharmaceutical Sciences)
Abstract Background Analytical quality by design approach is a systematic and scientific method for developing robust analytical procedures. Applying QbD principles in developing stability-indicating HPLC method for quantifying rosuvastatin and bempedoic acid in tablets enhances method understanding by identifying critical method parameters and analytical attributes, ensuring consistent quality. Method A two-level seven-factor Plackett–Burman design was employed to screen method parameters. Based on Pareto ranking analysis, the % aqueous (%v/v), buffer pH, and flow rate (ml/min) were identified as critical method parameters, while the retention times of rosuvastatin and bempedoic acid and resolution were selected as critical analytical attributes. Optimization was conducted using a two-level three-factor Box–Behnken design. The final optimized method utilized a Spursil C18 column (5 µm, 150 × 4.6 mm) with a mobile phase consisting of 15 mM ammonium acetate buffer (pH 6.0) and acetonitrile (40:60%v/v), a flow rate of 1 mL/min, and UV detection at 244 nm with an 8-min run time. Results Under the above conditions, rosuvastatin and bempedoic acid had retention times of 2.474 min and 3.396 min, respectively. Validation of the optimized method followed ICH Q2 (R1) guidelines and included system suitability, specificity, linearity, accuracy, precision, detection limit, quantitation limit, and robustness assessments. Linearity was observed in the range of 0.8–4.0 µg/mL for rosuvastatin and 3.6–18 µg/mL for bempedoic acid. Additionally, the greenness of the method was evaluated using AGREE software, which provided a score of 0.72, indicating compliance with Green Analytical Chemistry principles. Conclusion The developed RP-HPLC method is both sensitive and robust for the quantification of rosuvastatin and bempedoic acid in tablet formulations. The use of Plackett–Burman and Box–Behnken designs facilitated efficient optimization, and the method meets ICH guidelines and greenness criteria, confirming its suitability for routine analysis in quality control laboratories. Graphical Abstract